Examining the Integration of Environmental, Social, and Governance (ESG) Priorities Into Employer Value Proposition (EVP) : A Qualitative Investigation From An Employee Perspective - Andradi, Andradige; Eribo, Eghosa Ben (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2024)
This study investigates the integration of Environmental, Social, and Governance (ESG) priorities into Employer Value Propositions (EVPs) within the context of higher education institutions, specifically focusing on Swedish universities. The research aims to explore how ESG priorities are perceived and experienced by faculty and staff, and how these priorities align with employees' personal values and expectations. By addressing this gap, the study seeks to understand the impact of ESG integration on employee perceptions and the overall attractiveness of the university as an employer.The study employs a qualitative methodology, utilizing in-depth semi-structured interviews with faculty and staff members across multiple campuses of Luleå University of Technology (LTU). The interviews provide rich, contextual insights into the participants' views on the university’s ESG initiatives, including comprehensive environmental programs, strong social responsibility efforts, and ethical governance practices, along with the effectiveness of communication strategies in conveying these priorities.The findings reveal that these ESG initiatives significantly influence employees' perceptions of their university’s commitment to sustainable and ethical practices. Specifically, the integration of ESG priorities not only enhances employees' sense of pride and commitment but also fosters a positive work culture when these initiatives align with their personal values and expectations. The study identifies key areas where ESG efforts can be strengthened to further align with employee values, thereby shaping a compelling EVP that attracts and retains environmentally, socially, and ethically conscious talent.Theoretical implications include enhanced stakeholder alignment, while practical implications highlight improved employee engagement and satisfaction through ESG initiatives. The research contributes to the existing literature by filling the gap regarding the qualitative exploration of ESG integration in EVPs within the higher ...